2000
DOI: 10.1002/1520-6394(2000)12:1<44::aid-da6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone augmentation in treatment-resistant depression with fatigue and hypocortisolaemia: A case series

Abstract: Abnormalities of the hypothalamic‐pituitary‐adrenal (HPA) axis have long been implicated in major depression with hypercortisolaemia reported in typical depression and hypocortisolaemia in some studies of atypical depression. We report on the use of prednisone in treatment‐resistant depressed patients with reduced plasma cortisol concentrations. Six patients with treatment‐resistant major depression were found to complain of severe fatigue, consistent with major depression, atypical subtype, and to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
3
18
0
1
Order By: Relevance
“…We propose that antidepressants in humans could inhibit the steroid transporters localized on the BBB and in neurones, and thus increase the access of cortisol to the brain and the negative feedback on the HPA axis. This is consistent with studies showing that treatment with GR and MR agonists (Dinan et al, 1997;Bouwer et al, 2000), including cortisol (DeBattista et al, 2000), has antidepressant effects in humans. Hypothetically, the increased access of cortisol to the brain could balance the reduction of GR function described in patients with major depression (Pariante and Miller, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…We propose that antidepressants in humans could inhibit the steroid transporters localized on the BBB and in neurones, and thus increase the access of cortisol to the brain and the negative feedback on the HPA axis. This is consistent with studies showing that treatment with GR and MR agonists (Dinan et al, 1997;Bouwer et al, 2000), including cortisol (DeBattista et al, 2000), has antidepressant effects in humans. Hypothetically, the increased access of cortisol to the brain could balance the reduction of GR function described in patients with major depression (Pariante and Miller, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings further support the notion that one of the mechanisms by which antidepressants exert their therapeutic effects is by increasing the function of corticosteroid receptors and therefore normalizing HPA axis hyperactivity in depressed patients. This model is also consistent with clinical studies showing that treatment with MR and GR agonists, including prednisolone, has antidepressant effects in humans (Dinan et al 1997;Bouwer et al 2000;DeBattista et al 2000). We believe that enhanced cortisol action in the brain will prove to be a successful approach to maximise therapeutic antidepressant effects (Pariante 2003).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, in atypical depression and chronic fatigue it has been shown that corticosteroid (prednisone) augmentation may be useful [456]. There are some data suggesting that hypoactivity of the HPA axis and hypofunction of CRF neurons results in hyperimmune fatigue states such as chronic fatigue syndrome and atypical depression, e.g.…”
Section: Allostatic Load and The Immune Systemmentioning
confidence: 99%